Influence of remaining coronal thickness and height on biomechanical behavior of endodontically treated teeth: survival rates, load to fracture and finite element analysis (Journal of Applied Oral Science, 2022)
Objective: To evaluate the effect of restorative strategy (fiber post vs cast post and core), coronal height (0 mm vs 2 mm) and thickness (higher than 1 mm vs lower than 1 mm) on survival rate, fracture resistance and stress distribution. Material and Methods: Seventy-two bovine teeth were cleaned and allocated in six groups (n = 12). Twenty-four teeth were sectioned at 13 mm length (no remaining coronal structure) and forty-eight were sectioned at 15 mm (2 mm remaining coronal structure). Half of the forty-eight had remaining coronal thickness lower than 1 mm and the other half had thickness higher than 1 mm. All root canals were prepared at 10 mm (luting length), fiber posts were cemented in thirty-six specimens and cast post and core in other thirty-six. All teeth were restored with metallic crowns. Specimens were submitted to 1.5 million cycles (100 N, 45°, 10 Hz at 2 mm below incisal edge) and evaluated at each 500,000 cycles to detect failures. Specimens that survived were submitted to load to fracture test. Bidimensional (Rhinoceros® 4.0) models were obteined survival data submitted to Kaplan-Meier (α=0.05) analysis and load to fracture values submitted to ANOVA and Tukey tests (α=0.05). Results: Groups without remaining coronal structure showed survival rates lower than other groups (p=0.001). ANOVA showed higher values of load to fracture for groups with coronal thickness higher than 1 mm (p=0.0043). Finite element analysis showed better stress distribution in groups with remaining coronal structure and restored with fiber post. Conclusion: Specimens without remaining coronal structure have lower survival rates. Specimens with remaining structure lower than 1 mm and without coronal structure support the same load to fracture value independently of the restorative strategy.